Chemotaxonomy of the Lauraceae: N-Methyl-2,3,6 trimethoxymorphinandien- 7-one, the Major Alkaloid from Alseodaphne perakens'is - Lajis, Md Nordin; Mahmud, Zurina; Din, Laily; Toia, Robert F. (1989)
The leaves of Alseodaphne perakensis contain one major and a complex mixture of minor alkaloids. The major component was identified as N-methyl-2,3, 6-trimethoxymorphinandien-7-one by spectroscopic analyses of the parent compound, its methiodide salt and sodium borohydride reduction products.